TROMBOEMBOLIA PULMONAR - Proaño Lucero, Silvia Aracely (2023)
Acute pulmonary embolism (PE) is the occlusion of the pulmonary arteries by thrombi originating elsewhere, typically in the large veins of the legs or pelvis, is a form of venous thromboembolism (VTE), which is common and, in sometimes deadly The clinical presentation is usually variable and non-specific such as dyspnea, pleuritic chest pain, dizziness, syncope, cardiorespiratory arrest, tachypnoea, tachycardia, hypotension. Diagnosis is most often with computed tomography angiography (CT angiography), and ventilation/perfusion scintigraphy is sometimes necessary. Early diagnosis and treatment are essential to reduce mortality, initial management in case of suspicion is hemodynamic and ventilatory support, and initiation of anticoagulation. Definitive therapeutic alternatives include thrombolysis, embolectomy, but the decision must be individualized for each case. . We present the case of a 75-year-old female with a history of Cystopexy, intercurring with Upper Digestive Bleeding and requiring blood products, they perform Upper Digestive Endoscopy finding an ulcer in the FORREST IB-IIB Duodenal Bulb plus hemostatic clipping of the same, later presenting tachypnea, tachycardia. The CT angiography of the chest showed a 25mm thrombus in the right lower lobe branch, a 27mm thrombus in the ascending branch on the right side, millimeter thrombi of 5mm, 6mm and 10mm in the left pulmonary artery and left descending branches. For this reason, this review deals with the importance of suspecting it with a correct anamnesis and the establishment of treatment as soon as possible in case of suspicion.